Do Rational Use Meet Reality in a Country under Financial Assistance Program for Cost-saving Expenditures? The Two Sides of the Portuguese Coin - C Torre; C Torre; J Guerreiro; M Gomes; S Costa (Formifarma, LDA., 2019)
Background The Memorandum of Understanding (MoU) signed in 2011, between the Portugal (PT) and the European Commission, International Monetary Fund and the European Central Bank, imposed the establishment and monitoring of several prescribing guidelines. Objectives To perform a cross-country comparison of utilization patterns of ambulatory high expenditure therapeutic groups between PT and six European countries focusing on quality prescribing indicators (e.g. first-line uptake) and a cost-saving scenario analysis using potentially more rational prescribing patterns in PT. To investigate the impact of PT prescribing guidelines set forth by the MoU. Methods Cross-national drug utilization with 2012 data from: PT, Denmark, UK, Finland, the Netherlands, Norway and Sweden. Analysis comprised Oral Antidiabetic Drugs (OAD)(A10B), Antihypertensives (AHT) (C02,C03,C07,C08&C09), Lipid-Lowering Drugs(LLD)(C10AA&C10BA02), Proton Pump Inhibitors(PPI)(A02BC), Oral Anticoagulants (B01AA,B01AE&B01AF) and Antiepileptics-Carboxamide der.(N03AF). Data from PT was retrieved from hmR Pharmacy Sales Information System, a nationwide database with representative ambulatory data. Data from other countries was selected from open-access databases in each country. Cost-saving analysis: average annual cost per defined daily dose (DDD) from PT and simulations to measure the impact on total expenditure of studied European utilization patterns (%DDD) vs PT pattern. Segmented regression analyses were set up to investigate the impact of PT guidelines in the use for OAD, AHT, LLD and PPI (ref per: Jan2010-Sep2013). Results PT has the highest consumption of DPP-4 fixed-dose combinations (25.1%) Angiotensin Reception Blockers (32.3%) and Rosuvastatin (19.4%).Annual cost-savings were estimated in scenarios of more rational prescribing: e.g. 111.6M€, 83.5M€ when simulating the Dutch OAD and the Danish AHT prescribing patterns, respectively. Overall, the PT prescribing guidelines had no impact on first-line drugs uptake. Conclusions It is crucial to optimize prescribing patterns in PT, in order to achieve a more rational drug use and a sustained control of pharmaceutical expenditure. Published in: 30th International Conference on Pharmacoepidemiology and Therapeutic Risk Management (ICPE). 24-27 October 2014, Taipei, Taiwan.